2020
DOI: 10.1080/07853890.2020.1744708
|View full text |Cite
|
Sign up to set email alerts
|

Associations of serum sclerostin with bone mineral density, markers of bone metabolism and thalassaemia characteristics in adult patients with transfusion-dependent beta-thalassaemia

Abstract: Grudeva-Popova (2020) Associations of serum sclerostin with bone mineral density, markers of bone metabolism and thalassaemia characteristics in adult patients with transfusion-dependent beta-thalassaemia,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Several agonizing and antagonizing molecules involve in the regulation of this intricate pathway. 34 To date, many studies have assessed sclerostin, 16,17 another Wnt inhibitor, in various causes of osteoporosis including thalassemia, but only a few studies have evaluated serum Dkk-1 concentration in thalassemia. 18,35 Voskaridou et al found that adults with transfusion-dependent β-thalassemia vs. healthy controls had elevated concentrations of Dkk-1 and sclerostin, both of which were associated with lower BMD z-score at the lumbar spine, forearm and femoral neck.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several agonizing and antagonizing molecules involve in the regulation of this intricate pathway. 34 To date, many studies have assessed sclerostin, 16,17 another Wnt inhibitor, in various causes of osteoporosis including thalassemia, but only a few studies have evaluated serum Dkk-1 concentration in thalassemia. 18,35 Voskaridou et al found that adults with transfusion-dependent β-thalassemia vs. healthy controls had elevated concentrations of Dkk-1 and sclerostin, both of which were associated with lower BMD z-score at the lumbar spine, forearm and femoral neck.…”
Section: Discussionmentioning
confidence: 99%
“…Dkk-1 is an osteogenic cell-derived glycoprotein that inhibits Wnt/β-catenin signaling pathway, a key regulator of osteoblast function and bone formation. 15 In adults with β-thalassemia and TAO, increased sclerostin 16,17 and Dkk-1 18 concentrations were observed. Furthermore, serum Dkk-1 concentration was inversely associated with the lumbar spine (LS) BMD 18 as similarly observed in postmenopausal osteoporosis.…”
Section: Introductionmentioning
confidence: 97%
“…The results revealed a significant elevation in serum OPG levels among patients with osteoporosis compared to those without osteoporosis. Based on these findings, the study suggested that serum OPG could serve as a valuable marker for the early detection of osteoporosis in B-TM patients [8].…”
Section: Introductionmentioning
confidence: 88%
“…A study of 62 subjects with major BTH (32 males/30 females) showed that RANKL (receptor activator of nuclear factor kappa-Β ligand) was higher ( p = 0.049) and OPG (osteoprotegerin)/RANKL ratio was lower ( p = 0.009) in patients with BTH versus a group of menopausal osteoporotic women, with similar results for sclerostin and CTX (C-terminal telopeptide), which suggests that traditional medication against OP should not be different in TBD [ 97 ]. A study on adults with major BTH showed a 10-fold increase in serum sclerostin versus controls, being correlated with pre-transfusion Hb levels, LIC (Liver Iron Concertation), splenectomy status, and prevalent fractures [ 98 ]. Another study from 2022 confirmed lower OPG, a respective lower OPG/RANKL ratio in 60 children with transfusion-dependent BTH (aged between 5 and 14 y) versus 60 age—and sex- matched healthy subjects, with a higher incidence of OPG rs2073618 (×2.3) and OPG rs2073617 genotypes (×1.9) among TBD [ 99 ].…”
Section: Thalassemic Endocrine Diseasementioning
confidence: 99%